A Description of Advanced Chronic Kidney Disease Patients in a Major Urban Center Receiving Conservative Care. Issue 1 (11th July 2017) - Kamar, Fareed B.; Tam-Tham, Helen; Thomas, Chandra
Background: Conservative/palliative (nondialysis) management is an option for some individuals for treatment of stage 5 chronic kidney disease (CKD). Little is known about these individuals treated with conservative care in the Canadian setting. Objective: To describe the characteristics of patients treated with conservative care for category G5 non-dialysis CKD in a Canadian context. Design: Retrospective chart review. Setting: Urban nephrology center. Patients: Patients with G5 non-dialysis CKD (estimated glomerular filtration rate <15 mL/min/1.73 m 2 ). Measurements: Baseline patient demographic and clinical characteristics of conservative care follow-up, advanced care planning, and death. Methods: We undertook a descriptive analysis of individuals enrolled in a conservative care program between January 1, 2009, and June 30, 2015. Results: One hundred fifty-four patients were enrolled in the conservative care program. The mean age and standard deviation was 81.4 ± 9.0 years. The mean modified Charlson Comorbidity Index score was 3.4 ± 2.8. The median duration of conservative care participation was 11.5 months (interquartile range: 4-25). Six (3.9%) patients changed their modality to dialysis. One hundred three (66.9%) patients died during the study period. Within the deceased cohort, most (88.2%) patients completed at least some advanced care planning before death, and most (81.7%) of them died at their preferred place. Twenty-seven (26.7%) individuals died in hospital. Limitations: Single-center study with biases inherent to a retrospective study. Generalizability to non-Canadian settings may be limited. Conclusions: We found that individuals who chose conservative care were very old and did not have high levels of comorbidity. Few individuals who chose conservative care changed modality and accepted dialysis. The proportions of engagement in advanced care planning and of death in place of choice were high in this population. Death in hospital was uncommon in this population.